The Transformation of Qira’at in Classical Tafsir: A Comparative Study of Middle Eastern and Nusantara Manuscripts - Novendri S, Mochammad; Khairunnas Jamal; Hidayatullah Ismail; Dasman Yahya Ma'ali; Ali Musri Semjan Putra (STKQ Al-Hikam Depok, 2025)
The study of qiraat (variant Quranic readings) in classical exegesis is a significant aspect of Quranic studies, as differences in recitation can influence the interpretation of verses. This research explores how variations in qiraat found in classical tafsir manuscripts from the Middle East and the Malay-Indonesian archipelago (Nusantara) shape distinct exegetical patterns. Employing library research methods with philological and comparative approaches, this study analyzes several classical tafsir manuscripts, including Tafsir al-Qurtubi, Tafsir al-Tabari, Tafsir Tarjuman al-Mustafid, and Tafsir al-Ibriz. The findings reveal that qiraat not only create interpretive diversity but also influence the methodology of tafsir. Middle Eastern manuscripts tend to emphasize linguistic analysis and transmission chains (isnad), while Nusantara tafsir integrates qiraat with local cultural wisdom. This study contributes to a deeper understanding of qiraat-based interpretation and the intellectual transformation of Islamic scholarship across civilizations.